Development Application Cash Management In Tunas Mulia Bantar Gebang Foundation With The Extreme Programming Method - Intan Dwi Fatmaningtyas; Rita Wahyuni Arifin; Jafar Shadiq (Jurnal Mantik, 2021)
The use of information technology that is implemented through an information system provides convenience for its users. The convenience obtained in using this information system is to facilitate data management and data retrieval based on predetermined categories. This phenomenon also applies to the Tunas Mulia Bantar Gebang Foundation. This foundation is an organization that serves out-of-school children from waste scavenger families around the Bantar Gebang TPA. Tunas Mulia Bangsa Foundation activities have several humanitarian programs, one of which is opening schools for scavengers from early childhood to high school. The problems faced by Tunas Mulia Foundation are (1) it is still difficult to record donors who provide assistance, (2) difficulty in identifying the types of receipts received by the Foundation, (3) difficulty in providing information on cash receipts and disbursements to donors because data management is still conventional, (4) difficulties in calculating or recapitulating activities that have been carried out, and (5) the absence of a system that displays complete data and information regarding student sponsorship activities carried out by Tunas Mulia Foundation. This research uses Extreme Programming development model in using Extreme Programming with four stages. It is hoped that the application that will be developed can be a solution to the problems faced by the Foundation regarding the management of incoming and outgoing cash. The target output of this research can be published in accredited national journals indexed by Sinta, HKI, and application prototypes.